Chloroplast Genomes of Two Species of Cypripedium: Expanded Genome Size and Proliferation of AT-Biased Repeat Sequences - Guo, Yan-Yan; Yang, Jia-Xing; Li, Hong-Kun; Zhao, Hu-Sheng (Frontiers in Plant Science, 2021)
The size of the chloroplast genome (plastome) of autotrophic angiosperm is generally conserved. However, the chloroplast genomes of some lineages are greatly expanded. Here, we present the sequencing, assembly, and annotation of the chloroplast genomes of Cypripedium tibeticum and C. subtropicum. We de novo assembled the chloroplast genomes of the two species with the combination of short-read Illumina data and long-read PacBio data. The plastomes of the two species are characterized by expanded genome size, proliferated AT-rich repeat sequences, low GC content and gene density. The plastomes of C. tibeticum (197,815 bp) and C. subtropicum (212,668 bp) are substantially larger than those of the three species sequenced in previous studies. The plastome of C. subtropicum is the longest one of Orchidaceae to date. Despite the increase in genome size, the gene order and gene number of the plastomes are conserved, with the exception of an ~75kb large inversion in the large single copy (LSC) region shared by the two species. The most striking is the record-setting GC content in C. subtropicum (28.2%). Moreover, the plastome expansion of the two species is strongly correlated with the proliferation of the AT-biased noncoding regions: the noncoding content of C. subtropicum is in excess of 57%. The genus provides a typical example of plastome expansion induced by the expansion of noncoding regions. Considering the pros and cons of different sequencing technologies, we recommend hybrid assembly based on long and short reads applied to the sequencing of plastomes with AT-biased base composition. This study enriches the understanding of plastome expansion of angiosperms.